HUBUNGAN PERILAKU, LINGKUNGAN DAN PELAYANAN KESEHATAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS GERUNGGANG KOTA PANGKALPINANG (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
Dengue fever is one of the infections caused by the spreading of dengue virus carried by the Aedes Aegypty mosquitos. Based on the data from the Pangkalpinang City Health Office, the occurrence of dengue fever in Public Health Center Gerunggang shows the increasing rate over the last three years, namely in 2017 there were 15 cases. In 2018 there were 44 cases. Where as in 2019 there were 56 cases of dengue fever. This study aims to know the related factors towards the occurrence of dengue fever in the work area of Public Health Center Gerunggang. This research employs a case control research design.The sample are drawn using simple random sampling technique. The population of this research is the entire people in the work area of Public Health Center Gerunggang with the total number of 40,953 persons. The number of sample taken in this research is using 1 : 1 rate, which means the case samples are 56 persons, and the control samples are 56 persons. The result of this research shows that there are significant relations between variables of attitude with score (p=0.000 OR= 11.111), and environment (p=0.001 OR=4.167) with the occurrence of dengue fever in the work area of Public Health Center Gerunggang. Where as, there is no significant relation between the variable of health care service with score(p=0.097 OR= 2.200) with the occurrence of dengue fever in the work area of Public Health Center Gerunggang. From the result, the writer suggests the public to raise their awareness and participation towards the effort to prevent the occurrence of dengue fever, whether to do as personal or to cooperate with the medical officer. These efforts are needed to minimize the increase of dengue fever occurrence in their surroundings.